Survival model database of human digestive system cells exposed to electroporation pulses: An in vitro and in silico study - Han, Xuan; Zhang, Nana; Zhang, Yuchi; Li, Zhuoqun; Wang, Yingxue; Mao, Lujing; He, Tianshuai; Li, Qingshan; Zhao, Jiawen; Chen, Xue; Li, Yixuan; Qin, Zitong; et al. (Frontiers in Public Health, 2022)
Background and objectives This study aimed to establish a mathematical survival model database containing cell-specific coefficients from human digestive system cells exposed to electroporation pulses (EPs). Materials and Methods A total of 20 types of human digestive system cell lines were selected to investigate the effect of EPs on cell viability. Cell viability was measured after exposure to various pulse settings, and a cell survival model was established using the Peleg–Fermi model. Next, the cell-specific coefficients of each cell line were determined. Results Cell viability tended to decrease with the increase in electric field strength (EFS), pulse duration, and pulse number, but the decreasing tendency varied among different cell lines. When exposed to a lower EFS (<1000 V/cm), only a slight decrease in cell viability occurred. In contrast, when exposed to a short pulse duration and a low EFS, cell viability could even increase. All cell lines showed a similar tendency: the extent of electrical injury increased with the increase in pulse number and duration. However, there existed differences in heat sensitivity among organs. Conclusions This database can be used for the application of electroporation-based treatment in the digestive system to predict cell survival and tissue injury distribution during the treatment.